Light-to-Moderate Ethanol Feeding Augments AMPK-α Phosphorylation and Attenuates SREBP-1 Expression in the Liver of Rats - Srinivas Nammi; Basil D Roufogalis (Frontiers Media S.A., 2013)
Purpose: Fatty liver disease, a hepatic manifestation of metabolic syndrome, is one of the major causes of chronic liver diseases. Epidemiological studies suggest that regular light-to-moderate ethanol consumption lowers the risk of developing metabolic disorders including dislipidemia, insulin resistance, type 2 diabetes and fatty liver disease. However, the mechanism(s) of the protective effect of light-to-moderate ethanol consumption on the liver remains unknown. Methods: In the present study, we investigated the effects of light (6%, 0.94 g/kg/day) and moderate (12%, 1.88 g/kg/day) ethanol feeding in rats for 3 weeks on the circulating and hepatic biochemical profiles and on the hepatic protein expression and phosphorylation status of adenosine monophosphate-activated protein kinase-α (AMPK-α) and other down-stream targets of this enzyme including sterol regulatory element-binding protein-1 (SREBP-1), SREBP cleavage-activating protein (SCAP) and 3-hydroxy-3-methyl-glutaryl-CoA reductase (HMG-CoA reductase). Results: Despite no significant difference in food-intake among the groups, light ethanol treatment significantly increased the body weight compared to control rats. Serum glucose, insulin, total cholesterol, triglycerides, phospholipids and hepatic cholesterol and triglycerides were not significantly different among the groups. However, serum free fatty acids were significantly reduced with light ethanol treatment. Both light and moderate ethanol treatment significantly increased the hepatic levels of phosphorylated AMPK-α protein and this was associated with significant reduction of SREBP-1 protein expression, suggesting an enhanced fatty acid oxidation. In addition, light ethanol treatment significantly decreased the SCAP protein expression in the liver. However, liver HMG-CoA protein expression was not significantly different with ethanol consumption. Conclusion: Chronic light-to-moderate ethanol consumption increased AMPK activation which was associated with decreased expression of SREBP-1 and SCAP in the liver. Thus, our studies provide mechanistic evidence for the earlier epidemiological studies that indicate light-to-moderate ethanol intake lowers the risk of development of fatty liver disease and other metabolic disorders. Our studies demonstrate that the protective effects of light-to-moderate ethanol arise at least in part by increased phosphorylation of AMPK-α and decreased SREBP-1 expression in the liver. Further studies are warranted to determine the effects of light-to-moderate ethanol on intracellular up-stream and down-stream targets of AMPK and also on the implications of light-to-moderate ethanol in protecting non-alcoholic fatty liver disease.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.